A Preliminary Assessment of Stigma in Law Enforcement Officers’ Responses to Opioid Overdoses - Kruis, Nathan E. (Journal of drug issues, 2021)
Prior work has suggested that provider-based stigma of substance use disorders may be one barrier to fighting the opioid epidemic. However, to date, provider-based stigma has been afforded little attention in the context of the criminal justice system. The goal of the current study was to extend this line of research by examining the impact of provider-based stigma toward opioid using persons to beliefs about help that should be provided to persons experiencing an overdose among a sample of 208 police officers working in departments in the Northeastern Region of the United States. In addition, this study explores the relationship between provider-based stigma and the anticipated on-duty behavioral responses to opioid overdoses. Results from multivariable analyses indicate that certain dimensions of social stigma are significantly related to officers’ perceptions of help in varying directions, along with officers’ experiences with naloxone administration and departmental policy pertaining to the use of naloxone.